A mitigation strategy for commercial aviation impact on NOx‐related O3 change. Issue 14 (29th July 2016) - Wasiuk, D. K.; Khan, M. A. H.; Shallcross, D. E.; Derwent, R. G.; Lowenberg, M. H.
Abstract: An operational mitigation strategy for commercial aircraft impact on atmospheric composition, referred to as the turboprop replacement strategy (TRS), is described in this paper. The global air traffic between 2005 and 2011 was modeled with the TRS in which turbofan powered aircraft were replaced with nine chosen turboprop powered aircraft on all routes up to 1700 nautical miles (NM) in range. The results of this TRS double the global number of departures, as well as global mission distance, while global mission time grows by nearly a factor of 3. However, the global mission fuel and the emissions of aviation CO2, H2 O, and SOx remain approximately unchanged, and the total global aviation CO, hydrocarbons (HC), and NOx emissions are reduced by 79%, 21%, and 11% on average between 2005 and 2011. The TRS lowers the global mean cruise altitude of flights up to 1700 NM by ~2.7 km which leads to a significant decrease in global mission fuel burn, mission time, distance flown, and the aircraft emissions of CO2, CO, H2 O, NOx, SOx, and HC above 9.2 km. The replacement of turbofans with turboprops in regional fleets on a global scale leads to an overall reduction in levels of tropospheric O3 at the current estimated mean cruise altitude near the tropopause where the radiative forcing of O3 is strongest. Further, the replacement strategy results in a reduction of ground‐level aviation CO and NOx emissions by 33 and 29%, respectively, between 2005 and 2011. Key Points: Global aviation CO and hydrocarbons emissions are reduced by 79% and 21% with the mitigation strategy NOx and O3 are reduced near tropopause when turbofans are replaced by turboprops The replacement strategy results in a reduction of ground‐level aviation CO and NOx emissions by 33 and 29%, respectively